Modeling Fixed Income Securities and Interest Rate Options - Jarrow, Robert A. (Milton : CRC Press LLC, 2019)
Modeling Fixed Income Securities and Interest Rate Options, Third Edition presents the basics of fixed-income securities in a way that, unlike competitive texts, requires a minimum of prerequisites. While other books focus heavily on institutional details of the bond market, all of which could easily be learned "on the job," the third edition of this classic textbook is more focused with presenting a coherent theoretical framework for understanding all basic models. The author's unified approach--the Heath Jarrow Morton model--under which all other models are presented as special cases, enhances understanding of the material. The author's pricing model is widely used in today's securities industry. This new edition offers many updates to align with advances in the research and requires a minimum of prerequisites while presenting the basics of fixed-income securities. Highlights of the Third Edition Chapters 1-16 completely updated to align with advances in research Thoroughly eliminates out-of-date material while advancing the presentation Includes an ample amount of exercises and examples throughout the text which illustrate key concepts .
9.2 The Two-Factor Economy9.2.1 Complete Markets; 9.2.2 Risk-Neutral Probabilities; 9.2.3 Risk-Neutral Valuation; 9.2.4 Bond Trading Strategies; 9.3 Multiple Factor Economies; Appendix; References; Chapter 10 Contingent Claims Valuation -- Theory; 10.1 Motivation; 10.2 The One-Factor Economy; 10.2.1 Complete Markets; 10.2.2 Risk-Neutral Probabilities; 10.2.3 Risk-Neutral Valuation; 10.3 The Two-Factor Economy; 10.3.1 Complete Markets; 10.3.2 Risk-Neutral Probabilities; 10.3.3 Risk-Neutral Valuation; 10.4 Multiple Factor Economies; Appendix; Section III Applications; Chapter 11 Coupon Bonds
Description based upon print version of record.
11.1 The Coupon Bond as a Portfolio of Zero-Coupon Bonds
OCLC-licensed vendor bibliographic record.
Keywords: MATHEMATICS / General; MATHEMATICS / Applied; Fixed-income securities